Prevalance of anemia in children with acute lower respiratory tract infection: a case control study in children between 6 months to 23 months - Marol, Rajakumar N.; Marol, Rohitkumar R.; Marol, Renuka R. (International Journal of Contemporary Pediatrics, 2020)
Background: Anemia and ALRI are quite common in infants and toddlers in developing countries. ALRI is a leading cause of mortality in children below 5 years of age and it is important to prevent risk factors for development of ALRI. Present study was conducted to know the prevalence of anemia in children between 6 m to 23 m with ALRI and the relation between ALRI and anemia. Methods: This is a prospective case control study, conducted at Level 2 hospital situated in backward district over a period of 1 year. Two hundred cases who had ALRI as per WHO criteria and 200 controls were taken as the study group. Children were divided in to 3 different age groups. Haemoglobin level was estimated in all.Anemia was defined and classified according to WHO criteria. Results: Out of total 200 children both in cases and controls, 128 (64%) were males and 72 (36%) were females. Overall 190 (95%) of cases and 187 (93.5%) of controls had anemia. The prevalence of anemia was uniform in both sexes and all age groups. Children in the age group 6m -11m were more likely to develop ALRI. Conclusions: Prevalance of anemia in children between 6 m to 23 m with ALRI and without ALRI was 93.5% and 95% respectively. Authors cannot declare with affirmation that there was no association between Hb levels and ALRI as prevalence of anemia was very high in control group. Screening all children for anemia and taking proper intervention measures is necessary while treating for other ailments like ALRI.